The Problem of Abnormal Body Weight and Dyslipidemia as Risk Factors for Cardiovascular Diseases in Children and Adolescents with Type 1 Diabetes - Katarzyna Noras; Ewa Rusak; Przemysława Jarosz-Chobot (Journal of Diabetes Research)
Diabetes is a disease that affects many people around the world. Its complications are the cause of cardiovascular diseases (CVD) and increased mortality. That is why the search for predictive biomarkers is so important. The aim of the study was to show the prevalence of the problem and risk factors in children and adolescents with type 1 diabetes. These patients are often overweight and obese, and the percentage of lipid disorders is particularly high. The discussed markers of CVD risk in type 1 diabetes include apolipoproteins (apo-B and apo-C3), modified forms of LDL, and the role of high-density lipoprotein (HDL). Recently, a new look at the vasoprotective effect of HDL has appeared, which due to its dysfunctional form in type 1 diabetes may not protect against cardiovascular risk. The HDL proteome in type 1 diabetes has an altered protein composition compared to the healthy population. Another direction of research is determining the importance of trace elements (mainly Mg) in the development of diabetes complications.